China's evolving industrial policies and economic restructuring - Zheng, Yongnian; Tong, Sarah Y. (Sarah Yueting) (New York, NY : Routledge, 2014)
'China's recent phenomenal economic growth has been sustained primarily by China's rapid and continuous industrialisation. Currently industry accounts for over two-thirds of China's gross domestic product, and since 2009 China has been the world's largest exporter of manufactured products. This book explores the question of how far this industrial growth has been the product of government policies'--
Introduction / Yongnian Zheng and Sarah Y Tong -- Development of China's Industries and Industrial Restructuring / Yueping Wang -- Policy Evolution of China's Regional Development / Ding Lu -- China's Innovation Policy : Framework, Evolution and Trend / Xiaohua Duan and Rongfang Pan -- China's R&D Intensification and the Role of the State / Albert G Hu -- Openness, Productivity and Economic Growth in China / Yanrui Wu -- Why Are There so Many Automobile manufacturers in China? / Tomoo Markuwa -- Technological Capability Development in Complex Environments : The Case of the Chinese Telecom Equipment Industry / Xudong Gao and Jizhen Li -- Green Challenges and Keys to Sustain Growth of China's Electronic Information Industry / G.C. Alex Peng -- The Catching-up of China's ICT Industries : Recent Dynamics, Challenges, and Policy Implications / Xiaobo Wu, Wei Dou, and Yueqi Wang -- The Shale Gas Revolution and China's Industrial Policy / Mu Yang and Shenshen Cao -- China's Yangtze River Delta Region : Globalization, Production Networks and Regional Development / Yehua Dennis Wei -- Beijing-Tianjin-Hebei Development and the Transformation of Chinese Economy / Yongling Yao and Sarah Y Tong -- Achievement and Obstacles of China's Western Development / Houkai Wei -- China's Central Region : Development and Recent Strategies / Xiaobing Yang.
Includes bibliographical references and index.
Keywords: Industrial policy -- China; Industrialization -- China; China -- Economic policy; China -- Economic conditions -- 2000-